157 Supramarginal Resection Impact on Overall Survival for IDH-Wildtype Glioblastoma According to Their Cell Density Distribution and Infiltration Profile: A Mathematical Model. (1st April 2022) - Vivas-Buitrago, Tito; Domingo, Ricardo; Tripathi, Shashwat; De Biase, Gaetano; Ramos-Fresnedo; Desmond A. Brown, Andres; Akinduro, Oluwaseun; Sherman, Wendy; Sabsevitz, David S.; Bendok, Bernard R.; Parney, Ian F.; Chaichana, Kaisorn L.; Swanson, Kristin R.; et al.
Abstract : INTRODUCTION: Supramarginal resection of the T2-FLAIR beyond the T1 contrast enhancement has been suggested to further improve overall survival in glioblastoma (GBM) patients, with a potentially enhanced role in IDH-wildtype. GBMs present with high variability in tumor cell density, distribution, and infiltration patterns evidenced in imaging and histological analysis. Preoperative estimation of GBM grow kinetics with advanced mathematical models can provide further insight for surgical planning. METHODS: Volumetric measurements from T1 contrast-enhancing (CE) and T2-FLAIR regions of interest from retrospective pre and postoperative MRIs of patients that underwent a gross total resection of the CE were obtained. Tumor invasiveness profile (proliferation/diffusion (ρ/D) ratio) was calculated using the following formula: where VFL and VT1 are the preoperative FLAIR and contrast-enhancing volumes, respectively. Patients were then split into nodular (ND), moderately diffuse (MD), and highly diffuse (HD) subgroups based on their tumor invasiveness profile. SMR extension and survival analyses were performed among groups. RESULTS: 101 patients met the criteria for this study. Tumors were classified as ND (n = 34), MD (n = 34), and HD (n = 33) tumors. On multivariate analysis, increasing SMR had a significant positive correlation with OS only in MD and HD tumors (HR 0.98; 95% CI, 0.98–0.99; p = 0.05, and HR 0.98; 95% CI, 0.97–0.99; p = 0.02), respectively. On threshold analysis, OS benefit was seen with SMR from 10% to 29%, 10%-59%, and 30%-90%, for ND, MD, and HD, respectively. CONCLUSION: SMR impact on overall survival in this cohort of IDH-wildtype is significantly influenced by the degree of tumor invasiveness. The results of this study showed increased overall survival with increasing SMR for moderate and highly invasive tumors. Further analysis with SMR grouped in 10% intervals demonstrated an increase in overall survival for all groups, with a lower SMR extension to benefit nodular tumors.